2011
DOI: 10.1186/1752-153x-5-20
|View full text |Cite
|
Sign up to set email alerts
|

The ligational behavior of an isatinic quinolyl hydrazone towards copper(II)- ions

Abstract: BackgroundThe importance of the isatinic quinolyl hydrazones arises from incorporating the quinoline ring with the indole ring. Quinoline ring has therapeutic and biological activities whereas, the indole ring occurs in Jasmine flowers and Orange blossoms. As a ligand, the isatin moiety is potentially ambidentate and can coordinate the metal ions either through its lactam or lactim forms. In a previous study, the ligational behavior of a phenolic quinolyl hydrazone towards copper(II)- ions has been studied. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…It has also been shown that these metal complexes can be potent inhibitors of cell growth and DNA synthesis (Despaigne et al, 2010;Havanur et al, 2010;Ambwani et al, 2011). Metal complexes with hydrazones also have potential applications as catalysts, luminescent probes and molecular sensors (Seleem et al, 2011;Singh & Raghav, 2011). We report herein the crystal structure of the title compound, a new hydrazone.…”
Section: Data Collectionmentioning
confidence: 99%
“…It has also been shown that these metal complexes can be potent inhibitors of cell growth and DNA synthesis (Despaigne et al, 2010;Havanur et al, 2010;Ambwani et al, 2011). Metal complexes with hydrazones also have potential applications as catalysts, luminescent probes and molecular sensors (Seleem et al, 2011;Singh & Raghav, 2011). We report herein the crystal structure of the title compound, a new hydrazone.…”
Section: Data Collectionmentioning
confidence: 99%
“…In this study, the electronic absorption spectra of the hydrazone (2 × 10 -5 M) were recorded in solvents of various polarities (Table 1 and Figure 2 ). The hydrazone displays mainly three bands, the shortest UV- bands (λ 1 = 205-275 and λ 2 = 384-401 nm ) are best ascribed to π-π* transitions of the aromatic system and they are solvent sensitive bands whereas, the longest UV- band (λ 3 = 468-476 nm) is a strong broad band reflecting its charge transfer (CT) nature [ 9 , 10 ]. The latter band impacts the ligand its red color.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the band at 1610 cm −1 of υ(C=C) is still presented of the aromatic ring (Seleem, et al, 2011) (Table II).…”
Section: A the Ir Spectrum Of The Ligandmentioning
confidence: 99%